Beyond Beer's Law: Why the Index of Refraction Depends (Almost) Linearly on Concentration - Mayerhoefer, Thomas G.; Dabrowska, Alicja; Schwaighofer, Andreas; Lendl, Bernhard; Popp, Juergen (ChemPhysChem, 2020)
Beer's empiric law states that absorbance is linearly proportional to the concentration. Based on electromagnetic theory, an approximately linear dependence can only be confirmed for comparably weak oscillators. For stronger oscillators the proportionality constant, the molar attenuation coefficient, is modulated by the inverse index of refraction, which is itself a function of concentration. For comparably weak oscillators, the index of refraction function depends, like absorbance, linearly on concentration. For stronger oscillators, this linearity is lost, except at wavenumbers considerably lower than the oscillator position. In these transparency regions, linearity between the change of the index of refraction and concentration is preserved to a high degree. This can be shown with help of the Kramers–Kronig relations which connect the integrated absorbance to the index of refraction change at lower wavenumbers than the corresponding band. This finding builds the foundation not only for refractive index sensing, but also for new interferometric approaches in IR spectroscopy, which allow measuring the complex index of refraction function.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Absorbance; Beer's law; dispersion; index of refraction; vibrational spectroscopy